Manajemen Pembenihan Udang Vaname Litopenaeus vannamei di PT Central Proteina Prima, Kalianda, Lampung Selatan - Andri Iskandar; Afrizal Rizki; Andri Hendriana; Giri Maruto Darmawangsa; Abuzzar Abuzzar; Khoerullah Khoerullah; Muksin Muksin (Politeknik Negeri Lampung, 2021)
Vannamei Shrimp Litopenaeus vannamei is Indonesia's leading export commodity with high market demand and rapidly developing market prospects. Hatchery activities covered pond preparation, broodstock, brood spawning, egg removal, hatching eggs, naupli rearing, larvae rearing, natural feed culture, water quality management, pest and disease prevention, and larvae harvesting. The productivity from one parent of vaname shrimp is 300.000 eggs with FR 86 % and HR 85 %. The production of hatchery activities reached 2.607.428.880 shrimps year-1 consisting of 360 cycles. Production resulting from hatchery activities is post-larvae 4 and 7 with SR 75 %.